CURRENT SITUATION OF ENERGY JUSTICE AND ANALYSIS OF APPROACHES TO MEASURING ENERGY POVERTY: CASE STUDY OF BENIN(A REVIEW) - EKOUEDJEN, Evrard Karol; ADAMON, David G. F.; FAGBEMI, LATIF ADÉNIYI (My University, 2020)
Energy justice and energy poverty are booming concepts in West Africa and in Benin. This paper presents a literature review on both energy justice in Benin and on energy poverty measurement approaches. Evidence suggests that in developing countries, energy poverty is related to access to modern and affordable energy sources. They also indicate that energy injustices happen in Benin and are not perceived everywhere in the same way. Perception differs according to geographical location, social status and gender. Results showed that 60.63% of surveyed people hadn’t been consulted by the government about energy policies making. In the other hand, energy poverty is favored by low income, high energy costs and inefficiency or low energy efficiency. Beninese consumes very little electricity (about 3%), a lot of biomass (51%) and the rest in hydrocarbons (46%). According to (International Energy Agency, 2017) Benin has an electricity access rate of 32% compared with an average of 52% for West Africa. This rate is 11% in rural areas and 56% in urban areas. The multidimensional index of energy poverty (MEPI) reveals that Benin with a score of 0.83 is energy poor. It also shows that energy efficiency remains the surest way of improving energy justice. The disparities in access to energy noted will be measured in future studies with appropriate measurement methods adapted to the context of Benin that will be developed including equipments energy efficiency.
Keywords: Energy policies; Energy Justice; Energy; Poverty; Energy Efficiency; Developing; Countries